An integrated marketing communications campaign for Women's Philippine Basketball Association - Ramos, Camille Q. (Animo Repository, 2016)
This study intends to propose an integrated marketing campaign for the Women's Philippine Basketball Association (WPBA), the first ever professional basketball league for elite female basketball players in the Philippines. The WPBA is associated with the Philippine Basketball Association (PBA) The aim is to build awareness and hype to the PBA market regarding the presence of a basketball league for women. With the lack of exposure of women's basketball, sponsors may not be willing to take the risk in a new and untested investment. Women basketball players are still dreaming of having their own pro league while the men have it all. With these challenges for the league, the research proposes a campaign that will elicit WPBA brand awareness to the sports industry. This will also give a new kind of enthusiasm to the market through maximized marketing efforts linked to PBA. The campaign proposed runs for a six-month period and would focus on the following media: digital specifically social media, out-of-home, in-store marketing combined with sales promotions and public relations. At the end of the proposed campaign, it is expected that the WPBA will be considered as the league to watch where the consumers can expect high quality sports entertainment.